The Device of Ethylene Vinyl Acetate Sheet for Trismus Caused by Bilateral Mandible Fractures. (26th August 2021) - Ihara, Yoshiaki; Nakamichi, Yuka; Tashimo, Yuichi; Nozue, Shinji; Hayashi, Kota; Ishiguro, Mitsunori; Takahashi, Koji
Abstract : Trismus is commonly caused by temporomandibular joint disorders and maxillofacial fractures. We report the case of a 62-year-old woman with trismus and difficulty in mastication caused by bilateral mandibular fractures. She had a maximal interincisal opening distance (MID) of 22 mm. Mouth-opening training was administered using a novel dental mouth-training device custom-made using ethylene vinyl acetate sheets and according to the dentition and extent of mouth-opening of the patient. After 2 months of training, the MID increased to 42 mm. With adequate training, this device is effective in treating trismus due to scarring.